Carga y tipología microbiana relacionada con infecciones asociadas a la asistencia sanitaria en servicios clínicos (2018)
Introduction: Health care-associated infections have an impact on the quality of health care services, thus causing longer stay at hospitals, rise in assistance costs and risks for the patient’s life. Despite the attempts at improving this situation, the problem still remains. Objective: To determine the microbial burden and typing related to health care-associated infections in the clinical services. Methods: A quantitative, descriptive, correlative and non-experimental design-type study conducted in the Surgery services and in the Intensive Care Unit of a hospital located in Santa Marta, Colombia, from April to September, 2014. The lab samples were intentionally taken from patients, workers, physical spaces and equipment. The information analysis was based on absolute and relative frequencies as well as Pearson’s correlation coefficient. Results: The Surgery Services reported surgical wound infection (100 %), isolation of Pseudomona aeruginosa in 66.66 % of cases; five bacteria-positive physical spaces (60 % to coagulase-negative Staphylococcus albus and 40 % to Streptococcus spp). Two pieces of equipment were positive to coagulase-negative Staphylococcus albus. The Intensive Care Unit reported urinary infections (40 %), pneumonia (40 %) and surgical wound (20 %), being Acinetobacter baumannii (40 %) the most frequent. In all the positive physical spaces, Streptococcus spp was isolated, but not a single germ was found in the medical instruments or in the equipment. Conclusions: Surgical Service had higher microbial burden than the Intensive Care Unit. The predominant germ was Acinetobacter baumanni. The correlation among the causative germ of health care-associated infections, the physical spaces and the biomedical equipment was poor whereas the correlation of the causative germ and the surgical instruments was non-existent. © 2019 Revista Cubana de Enfermería.